Designing Jawi typeface to enhance the quality of modern design / Mohamed Razeef Abdul Razak...[et.al] - Abdul Razak, Mohamed Razeef; Md. Zain, D’zul Haimi; Harun, Azahar; Che Cob, Saiful Akram; Mohd. Radzuan, Lili Eliana (2016)
The use of Jawi script is mandatory on billboards and signage especially in the state of Kelantan and Terengganu. The idea of having Jawi script on billboard and signage is to uplift the old malay script and also by employing Jawi script it will nurture Islamic spiritual sense among Malay. However the Jawi typeface that is displayed on the advertising media (billboard, poster, bunting) normally do not complement the visual content, hence making jawi script outdated. This is because of limitation on the choice of typeface that is available for designer to complement Jawi script with modern design. The closest to Jawi typeface available is in Arabic setting which doesn’t include letters such as “cha”, “pa”, “ga”, “va” and “nya’. By designing a modern sets of of Jawi typeface, it is hope that consumer will not only read the content (message, images, graphic) on the advertising media but also appreciate and realise the importance of Jawi script in context of Malay heritage.